A systematic review of outcomes in postoperative pain studies in paediatric and adolescent patients: towards development of a core outcome set. (8th January 2018) - Ross, A.; Young, J.; Hedin, R.; Aran, G.; Demand, A.; Stafford, A.; Worley, J.; Moore, M.; Vassar, M.
Summary: Systematic reviews of postoperative pain in children have called into question the consistency of outcomes measured by clinical triallists as well as the measurement instruments used for assessment. Core outcome set methodology may be a solution to improve standardisation. This study provides an evidence‐based foundation for the development of a core outcome set for paediatric postoperative pain studies. We searched ClinicalTrials.gov to identify relevant postoperative pain studies in children. The search yielded 300 registered trials. The following data were then extracted from each of the trials: phase of trial; study type; study design; sample size; all outcomes; whether the outcome was listed as primary, secondary, or tertiary; the measurement instrument for each reported outcome; the specific metric for each outcome; and the type of clinical procedure. Following screening, 134 studies were included in our study. Pain measurement was the most commonly reported outcome (n = 123), followed by total postoperative analgesic dosage (n = 83) and side‐effects (n = 25). Temporal trends indicated that pain assessment and unexpected events increased in use between 2000 and 2016, whereas postoperative analgesia measurement decreased. We found a lack of standardisation among outcomes and measurement instruments in paediatric postoperative pain studies. Development of a core outcome set may improve the quality of future trials and allow for more accurate study‐to‐study comparisons.